Effect of pressing pressure on physical and mechanical properties of ELAEIS GUINEENSIS fronds composite board - Ellisha Iling; Dayang Siti Hazimmah Ali; Mohd Shahril Osman (Penerbit Universiti Kebangsaan Malaysia, 2019)
Performance of composite boards usually depends on the raw materials selection and fabrication parameters. This paper presents the effect of different level of applied pressure towards the performance of the end product of Elaeis guineensis composite board. The OPF was collected from a private plantation in Sarawak and refined into smaller particles by using a crusher machine. Sieved OPF particles that retained on the 0.60mm sieve mesh were used to fabricate composite boards with a targeted density of 0.7g/cm3. The 20 cm × 20 cm × 0.50 cm composite boards were fabricated under same hot press temperature of 160℃ for three different applied pressures of 5MPa, 6MPa, and 7MPa respectively. The physical and mechanical properties test were conducted according to the Japanese Industrial Standard (JIS A5908:2003). It is indicated from the results that the performance of Elaeis guineensis composite board improved with increasing applied pressure. The composite boards satisfied the provision set for the internal bond (IB) strength and modulus of rupture (MOR) in JIS A5908:2003. Unfortunately, the thickness swelling percentage exceeded the maximum set value. Overall performance investigated that Elaeis guineensis composite board is suitable to be used in indoor applications such as based materials, decorative boards, and teaching aids.